PHYSICAL EDUCATION IN THE UNITED STATES (A CRITICAL REFLECTION ON CURRENT STATUS AND FUTURE RESEARCH AGENDA) - Setiawan, Caly (Universitas Negeri Semarang (Unnes), 2016)
This paper explores the experiences of the author about living the discourse of physical education (PE) and physical education teacher education (PETE). More specifically, it focuses on the future of physical education in the United States will look like on its current path and how the author?s views differ and/or match published perspective. The author position statement is also supported by research to look for path physical education and PETE in the US should take and ultimately what it will look like at the end of that path. There also exist some research areas the US PE need to focus more or less on physical education and PETE. The author proposes some essential research questions about physical education and PETE that deserve investigation. The last part of the paper offers specific aspects of physical education and PETE practices that warrant special attention; barriers that have impeded research in the areas, and change to overcome such barriers.Artikel ini mengeksplorasi pengalaman penulis dalam menyelami wacara pendidikan jasmani dan pendidikan keguruan pendidikan jasmani. Secara lebih khusus, makalah ini memfokuskan pada masa depan pendidikan jasmani di Amerika Serikat sebagaimana saat ini sedang berada di jalannya dan bagaimana pandangan penulis berbeda dan/atau sesuai dengan perspektif literature. Posisi pernyataan penulis juga didukung oleh penelitian untuk melihat jalan yang harus ditempuh oleh pendidikan jasmani dan pendidikan keguruannya dan pada akhirnya bagaimana bagaimana bentuknya di akhir perjalanan. Beberapa area penelitian juga diidentifikasi di mana peneliti seyogyanya memfokuskan perhatiannya. Penulis mengusulkan beberapa pertanyaan penelitian yang esensial tentang pendidikan jasmani yang harus diteliti. Bagian akhir dari makalah ini menawarkan aspek praktis pendidikan jasmani dan pendidikan keguruan yang harus diperhatikan, berikut hambatan dan perubahan-perubahan untuk mengatasi hambatan tersebut.